Answer:
![x^(4) - 7x^(2) -26x-40](https://img.qammunity.org/2019/formulas/mathematics/high-school/zk4yf6smwyzt03qiuan80uaguqztwn6840.png)
Explanation:
The polynomial will be a fourth degree polynomial.
Let's take x = 4, then one of the factors is x - 4.
Then if x = -2, then the factor will be:
x + 2 = -2+ 2
x + 2 = 0
Then one of the polynomials is x + 2
Using the conjugate theorem:
if x = -1 + 2i, then -1-2i will be the root.
Then if x = -1+ 2i, then the factor of the function will be x- 1- 2i
Similarly, if x = -1-2i, then the factor x -(-1-2i)
This gives the final expression:
![x^(4) -7x^(2) -26x-40](https://img.qammunity.org/2019/formulas/mathematics/high-school/64nruf6wu12nhdb8r3qk4cx66voagzueqj.png)